Utilization of Local Natural Dyes and Mordants in Dyeing Polyester Yarn for Timor Woven Fabrics: Characterization and Potential Applications - Marselina Theresia Djue Tea; Elisabeth Korbafo; Faustinus Kadha; Yohana Ivana Kedang; Fetronela Rambu Bobu; Agustina Mogi; Ernesta Wae; Janrigo Klamegio Mere; Gebhardus Djugian Gelyaman (Postgraduate, University of Mataram, 2026)
The objective of this study was to extract natural dyes from plant parts, characterize them, and evaluate their color fastness properties. The yarns were bleached using hydrogen peroxide at a concentration of 10% (based on fiber weight) at 100°C for 30 minutes. Three natural dyes (teak leaves, turmeric, and mango bark) were selected as natural sources for color extraction, which was carried out for 60 minutes at 100°C. Dyeing was performed both with and without the addition of salt, alum, and lime as mordants. The FTIR spectra of fabrics dyed with natural dye extracts showed absorption bands at 2963–2918 cm⁻¹, indicating the presence of C-H stretching from methyl (CH₃) and methylene (-CH₂-) groups found in polyester. The band at 1710–1713 cm⁻¹ originated from the carbonyl (C=O) group, which is a main characteristic of polyester. The band around 1504–1577 cm⁻¹ was identified as aromatic C=C bond stretching. The band at 1338–1242 cm⁻¹ indicated C-O stretching, which may be attributed to ester groups in polyester. The band at 1091–1015 cm⁻¹ represented C-H bending, which is also characteristic of polyester molecules. Turmeric and teak leaves demonstrated better color fastness compared to mango bark.